(untitled) (ModaPalavra e-periódico, 2024)
The present investigation indicates the methodological approach of “Design Research through Practice” presented by Ilpo Koskinen (et. al., 2011) and introduced by Christopher Frayling (1993), illustrated with examples of the different kinds of academic researches specifically focused on the field of fashion design. Koskinen organizes and presents three cathegories of research in design that has the practice as a central element of the process: “Lab”, “Field” and “Showroom”. Based on the principles established by these authors, we present examples that illustrates different ways of combining theory and practice research while building academic knowledge in the field of fashion and textiles.